Emil and the detectives - Kastner, Erich (UK : Puffin Book, 2015)
A German boy and his friends use their ingenuity to catch a thief.
School Library Journal
5.0
3-6.
3-6
Keywords: Mystery and detective stories; Mystery fiction; Germany -- Fiction; Germany -- Fiction